PANDANGAN GURU PENDIDIKAN JASMANI SMATERHADAP PENERAPAN MODEL PEMBELAJARANTEACHING GAMES FOR UNDERSTANDING - Nur Sita Utami Soni Nopembri (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2011)
AbstractThe purpose of this research was to describe Physical Education teachers’ views on the application of theTeaching Games for Understanding Learning Model in Senior High Schools. This research was a case studyusing mixed methodology design proposed by John W. Creswell. The subjects of this research were 19 PhysicalEducation teachers in Senior High Schools who joined Socialization and Workshop of Teaching Games forUnderstanding. The researchers used all subjects to be respondents in collecting data using questionnaire.However, in collecting data by using interview, observation, and documentation, the researchers only used fivesubjects who were drawn by using purposive sampling technique. The researchers used triangulation of thedata collection technique so that the instruments used were questioners, interview guidelines, field notes, voicerecorder, and handy cam. Quantitative data were analyzed by scoring the result of the questionnaire. Meanwhilequalitative data were analyzed by using Miles and Huberman model. The result of this research showed that 19respondents (100%) had a positive view on the application of Teaching Games for Understanding in Senior HighSchools. This quantitative data was supported by data collected from interview, observation, and documentation.The results showed that teachers were enthusiastic with the Teaching Games for Understanding concept. Theyconsidered that the Teaching Games for Understanding Model was effective and efficient to be used in thelearning process. They were also enthusiastic when they taught using Teaching Games for Understandingmodel. It showed that they supported the development of Teaching Games for Understanding in Senior HighSchools. However, they had less ability to explain the concept of Teaching Games to Understanding to the otherpeople. As a result, they were doubt to use this model in the Physical Education teaching-learning process.Keywords: Physical Education, Teaching Games for Understanding, Teacher.AbstractTujuan dari penelitian ini adalah untuk menggambarkan pandangan guru Pendidikan Jasmani dalam penerapanModel Teaching Games for Understanding pada Pembelajaran di Sekolah Menengah Atas. Penelitian inimerupakan studi kasus dengan menggunakan desain metodologi campuran yang diusulkan oleh John W.Creswell. Subyek penelitian ini adalah 19 guru Pendidikan Jasmani di Sekolah Menengah Atas yang bergabungdalam Sosialisasi dan Workshop Teaching Games for Understanding. Para peneliti menggunakan semuaguru penjas untuk menjadi responden dalam pengumpulan data menggunakan kuesioner. Namun, dalammengumpulkan data dengan menggunakan wawancara, observasi, dan dokumentasi, peneliti hanyamenggunakan lima orang subjek yang diambil dengan menggunakan teknik purposive sampling. Para penelitimenggunakan teknik triangulasi pengumpulan data sehingga instrumen yang digunakan adalah penanya,pedoman wawancara, catatan lapangan, perekam suara, dan kamera. Data kuantitatif dianalisis dengan darihasil kuesioner. Sementara data kualitatif dianalisis dengan menggunakan Miles dan model Huberman. Hasilpenelitian ini menunjukkan bahwa 19 responden (100%) memiliki pandangan positif pada penerapan PermainanPengajaran Pemahaman di SMA. Ini data kuantitatif didukung oleh data yang dikumpulkan dari wawancara,observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru sangat antusias dengan PermainanPengajaran untuk Memahami konsep. Mereka menganggap bahwa model Teaching Games for Understandingefektif dan efisien untuk digunakan dalam proses pembelajaran. Mereka juga antusias ketika mereka diajarkanmenggunakan Pengajaran Permainan untuk Memahami model. Ini menunjukkan bahwa mereka mendukung